PGAP3 is expressed at increased levels in asthmatic ASM and is associated with increased ASM proliferation, contractility and expression of GATA3 and ALOX5 - Eric Leslie; Marina Miller; Allison Lafuze; Sofya Svyatskaya; Gil-Soon Choi; Joshua L. Kennedy; Yung-An Huang; Taylor A. Doherty; David H. Broide (PLoS ONE, 2025)
Post-GPI Attachment to Proteins phospholipase 3 (PGAP3) is a glycosylphosphatidylinositol (GPI) anchor-remodeling gene found on chromosome 17q12-21, which is a locus highly linked to asthma. Genetic association studies have linked PGAP3 SNPs to increased PGAP3 expression as well as asthma exacerbations, severity, and susceptibility. This study compared the levels of PGAP3 mRNA expression quantitated by RT-qPCR in human bronchial airway smooth muscle cells derived from postmortem lungs of asthmatics (ASM-A) to that derived from control non-asthmatics (ASM-NA). ASM-A expressed significantly higher levels of PGAP3 mRNA compared to ASM-NA. As ASM-A expressed higher levels of PGAP3 mRNA we performed functional studies of ASM-NA transfected with PGAP3 to determine if increased PGAP3 expression in ASM influenced ASM function including proliferation and contractility. Functional studies of ASM transfected with PGAP3 demonstrated that increased PGAP3 expression in ASM resulted in increased ASM proliferation and contractility. RNA-seq studies of ASM transfected with PGAP3 demonstrated significantly increased levels of genes linked to asthma including GATA3 and ALOX5. Fifteen genes upregulated by PGAP3 in ASM-NA were detected in asthmatic ASM data sets, underscoring the ability of PGAP3 to induce genes of importance to asthma in ASM. In summary, this study made the novel observation that ASM derived from the lungs of asthmatics express higher levels of PGAP3 compared to non-asthmatics. In addition, when ASM from non-asthmatics are transfected with PGAP3, the increased levels of PGAP3 increase ASM proliferation and contractility, and increase levels of genes previously linked to asthma including GATA3 and ALOX5. Overall, these studies suggest that increased PGAP3 expression in ASM plays a functional role in contributing to the pathogenesis of asthma.